Analisis Tematik Tafsir Kitab Fi Zilal al-Quran: Aspek Pemikiran Sosial dan Haraki: Thematic Analysis of Book Tafsir Fi Zilal al-Quran: Aspect of Social and Dynamic Thought - Tasnim Abdul Rahman; Amir, Ahmad Nabil (Journal of Quranic Sciences and Research, 2024)
Malay:Artikel ini mengkaji metode tafsir Sayyid Qutb dalam Kitab Fi Zilal al-Qur’an, khususnya pendekatan sosial-budaya dan haraki. Ia bertujuan mengidentifikasi aliran tafsir yang dikembangkan dan perannya dalam memproyeksikan pandangan dunia Islam yang moden berasaskan tafsiran sosialnya. Melalui metode kualitatif berbasis analisis literatur, penelitian ini menemukan bahwa tafsir ini menekankan nilai tauhid dan pengaruhnya terhadap pembentukan generasi Islam moden. Falsafah dan manhaj tafsir yang digariskan oleh Sayyid Qutb terkesan berdimensi haraki yang relevan dengan narasi dakwahnya yang moden berhaluan adabi ijtima‘i. English:The paper analysed the essential methodology adopted by Sayyid Qutb in his Book of Tafsir Fi Zilal al-Qur’an and its instrumental role in projecting modern Islamic outlook based on his social andynamic exegetical orientation. Its objective is to identify the exegetical school he propounded and its role in shaping modern Islamic worldview based on his social interpretation. The study is based on qualitative approaches in the form of literature survey. The finding shows that Sayyid Qutb had formulated an inclusive method of philosophical interpretation of the Qur’an that established socio-linguistic and ethico-legal principles as its core ideological roots and basis. The pattern of thought and interpretation were influenced by this idea reflecting the dynamic (haraki) framework it conceived in the development of his tafsir. This categorically form the basis of his philosophy and idealism underlying its socio-religious outlook and its relevance in the shaping of modern Islamic generation to revitalize the cultural-linguistic aspect and perennial values of tawhid in modern narrative of dakwah.